Pengembangan Model Kemitraan dan Pemasaran Terpadu Biofarmaka dalam Rangka Pemberdayaan Masyarakat Sekitar Hutan di Kabupaten Sukabumi, Provinsi Jawa Barat - Leti Sundawati; Ninuk Purnaningsih; Edy Djauhari Purwakusumah (Institut Pertanian Bogor, 2012)
Most of the community surrounding forest areas in Sukabumi District are poor farmers. They traditionally cultivate medicinal plants. However, quality of the products is not standardized, and hence, low price. Therefore, it is needed to strengthen and empower the farmer capacity, by developing an integrated marketing model for medicinal plants and by enhancing the competitiveness of the farmer group institution so that they can build a partnership with industry. This activity involved farmers at Mekarjaya Village, Ciemas Subdistrict who are member of Srijaya Farmer Groups Association. Survey, in-depth interview, and focus group discussion were conducted to get data on the existing condition. Farmer institution strengthening was conducted through trainings for farmers on entrepreneurship, medicinal plant cultivation and processing, facilitation of farmer group institution, and establishment of demonstration plots of medicinal plant cultivation. Agribusiness networking and partnership was built through the memorandum of understanding on marketing between Sri Jaya with two biopharmaca companies.